Dynamical Downscaling of CO2 in 2016 Over the Contiguous United States Using WRF‐VPRM, a Weather‐Biosphere‐Online‐Coupled Model. (6th April 2020) - Hu, Xiao‐Ming; Crowell, Sean; Wang, Qingyu; Zhang, Yao; Davis, Kenneth J.; Xue, Ming; Xiao, Xiangming; Moore, Berrien; Wu, Xiaocui; Choi, Yonghoon; DiGangi, Joshua P.
Abstract: Ecosystem function (particularly CO2 fluxes and the subsequent atmospheric transport), synoptic‐scale weather (e.g., midlatitude cyclones), and interactions between ecosystems and the atmosphere can be investigated using a weather‐biosphere‐online‐coupled model. The Vegetation Photosynthesis and Respiration Model (VPRM) was coupled with the Weather Research and Forecasting (WRF) model in 2008 to simulate "weather‐aware" biospheric CO2 fluxes and subsequent transport and dispersion. The ability of the coupled WRF‐VPRM modeling system to simulate the CO2 structures within midlatitude cyclones, however, has not been evaluated due to the lack of data within these weather systems. In this study, VPRM parameters previously calibrated off‐line using eddy covariance tower data over North America are implemented into WRF‐VPRM. The updated WRF‐VPRM is then used to simulate spatiotemporal variations of CO2 over the contiguous United States at a horizontal grid spacing of 12 km for 2016 using an optimized downscaling configuration. The downscaled fields are evaluated using remotely sensed data from the Orbiting Carbon Observatory‐2, Total Carbon Column Observing Network, and in situ aircraft measurements from Atmospheric Carbon and Transport‐America missions. Evaluations show that WRF‐VPRM captures the monthly variation of column‐averaged CO2 concentrations (XCO2 ) and episodic variations associated with frontal passages. The downscaling also successfully captures the horizontal CO2 gradients across fronts and vertical CO2 contrast between the boundary layer and the free troposphere. WRF‐VPRM modeling results indicate that from May to September, biogenic fluxes dominate variability in XCO2 over most of the contiguous United States, except over a few metropolitan areas such as Los Angeles. Plain Language Summary: Global warming due to increase in greenhouse gases, particularly CO2, is well known as a critical issue facing humanity. CO2 concentration increased quickly over the past two centuries, with the overall trend largely due to fossil fuel emissions. Year‐to‐year variations in CO2 growth rate are not well understood, which is partially due to uncertainty in terrestrial CO2 fluxes. Accurate estimation of terrestrial CO2 fluxes is limited by land cover and land use changes, drought, and weather influences. These factors/processes and their impact on CO2 fluxes and atmospheric mole fractions can be investigated using a weather‐biosphere‐online‐coupled model. The Vegetation Photosynthesis and Respiration Model (VPRM) coupled with the Weather Research and Forecasting (WRF) model (referred to as WRF‐VPRM) is one such tool. In this study, optimal VPRM parameters are implemented into WRF‐VPRM. The updated WRF‐VPRM is then used to simulate CO2 mole fractions over the United States for 2016. The simulation is evaluated using aircraft measurements and remote sensing data. Evaluations show that WRF‐VPRM captures the temporal variation of CO2 concentrations, as well as the horizontal CO2 gradients across fronts and vertical CO2 contrast in the low troposphere. Simulations using this modeling system can be used to help understand regional to global CO2 budgets. Key Points: The simulation is evaluated using CONUS‐scale, long‐term data, and in situ measurements that resolve the structures of midlatitude cyclones WRF‐VPRM is shown to reproduce the structures in CO2 mole fractions observed within midlatitude cyclones From May to September, biogenic fluxes dominate variability in XCO2 over most of the CONUS except around a few metropolitan areas such as LA